Pola Lanskap Permukiman Tradisional Masyarakat Adat Kampung Tegaldeeng, Desa Medalsari, Kabupaten Karawang - Nugrahatama, Davin; Gunawan, Andi; Pratiwi, Prita Indah (http://arl-faperta.ipb.ac.id/, 2024)
Tegaldeeng is one of the kampongs in the village of Medalsari, Karawang Regency, which has been influenced by the regency developments, so that it has an impact on the culture and the landscape. The landscape of Tegaldeeng kampong has very high potential in terms of natural and cultural resources. Efforts to prevent the degradation of the culture and the potential of the traditional landscape need to be studied in the kampong landscape pattern. This study aims to identify and analyze the character of the landscape and the elements that make up the settlement landscape, and to compose the landscape pattern of Tegaldeeng kampong based on local culture. This research was conducted using descriptive method through literature study, interview, and field observation. The settlement character of Tegaldeeng kampong landscape is relatively flat in the settlement area, and slightly undulating outside the area. The dominant land cover is rice fields and mixed gardens. The character is formed by supporting elements in the form of natural and artificial elements. Natural elements function more as a 'borrowing landscape' for the settlement landscape, except for the river that crosses the western village border. The man-made elements include rice fields, mixed gardens, settlements, and main road. The landscape of Tegaldeeng kampong settlement forms a cluster patterns, and able to accommodates all cultural activities of the local community.